# Solve for t -3(-4t+5)=-21

-3(-4t+5)=-21
Divide each term by -3 and simplify.
Divide each term in -3(-4t+5)=-21 by -3.
-3(-4t+5)-3=-21-3
Cancel the common factor of -3.
Cancel the common factor.
-3(-4t+5)-3=-21-3
Divide -4t+5 by 1.
-4t+5=-21-3
-4t+5=-21-3
Divide -21 by -3.
-4t+5=7
-4t+5=7
Move all terms not containing t to the right side of the equation.
Subtract 5 from both sides of the equation.
-4t=7-5
Subtract 5 from 7.
-4t=2
-4t=2
Divide each term by -4 and simplify.
Divide each term in -4t=2 by -4.
-4t-4=2-4
Cancel the common factor of -4.
Cancel the common factor.
-4t-4=2-4
Divide t by 1.
t=2-4
t=2-4
Simplify 2-4.
Cancel the common factor of 2 and -4.
Factor 2 out of 2.
t=2(1)-4
Cancel the common factors.
Factor 2 out of -4.
t=2⋅12⋅-2
Cancel the common factor.
t=2⋅12⋅-2
Rewrite the expression.
t=1-2
t=1-2
t=1-2
Move the negative in front of the fraction.
t=-12
t=-12
t=-12
The result can be shown in multiple forms.
Exact Form:
t=-12
Decimal Form:
t=-0.5
Solve for t -3(-4t+5)=-21

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top